Hydrogen sulfide prevents postoperative adhesion in a rat uterine horn model - Ye Xia; Yi Zhun Zhu; Congjian Xu (Elsevier, 2017)
Objective: Abdominal adhesions are primarily severe postoperative complications that can cause gynecological problems such as infertility and chronic pelvic pain. Inflammatory mediators are significantly related to adhesion formation, and hydrogen sulfide plays a significant anti-inflammatory role in multiple physiological processes. Therefore, the effect of NaHS, a hydrogen sulfide donor, on postoperative adhesion formation was examined in a rat uterine horn model. Materials and methods: A rat uterine horn model was created to evaluate whether NaHS, a hydrogen sulfide donor, could decrease postoperative adhesion formation. Rats were randomly grouped and administrated with different doses of NaHS, where DL-propargylglycine and low-molecular-weight heparin acted as negative and positive controls, respectively. The extent and severity of adhesions were assessed on the 14th postoperative day. Serum of rats was sampled for the determination of 27 cytokines using a chip. Results: The severity and total scores of adhesion in rats given 112μM/kg and 56μM/kg NaHS were significantly less compared with those of the control group (p<0.01). Scores for the extent of adhesion re-formation in the DL-propargylglycine and control groups did not differ (p>0.05). At least six cytokines were involved in the procedures for the prevention of adhesion formation, as they varied significantly among different groups. Conclusion: Administration of NaHS could apparently reduce postoperative adhesion in the rat uterine horn model. This preventive effect may be associated with the variation of cytokine that is related to inflammatory.